If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12(2x+1)-14.5(8x+2)=3(x-4)
We move all terms to the left:
12(2x+1)-14.5(8x+2)-(3(x-4))=0
We multiply parentheses
24x-116x-(3(x-4))+12-29=0
We calculate terms in parentheses: -(3(x-4)), so:We add all the numbers together, and all the variables
3(x-4)
We multiply parentheses
3x-12
Back to the equation:
-(3x-12)
-92x-(3x-12)-17=0
We get rid of parentheses
-92x-3x+12-17=0
We add all the numbers together, and all the variables
-95x-5=0
We move all terms containing x to the left, all other terms to the right
-95x=5
x=5/-95
x=-1/19
| -3(2a-3)+2=34(a+7) | | 12-22(2x+1)=4(x-1) | | 5x+46=18x | | 3.25(2x-3)+0.5=22.2 | | 3x+26+5x-11=11x-6 | | 1+5x=90 | | 40x=160-20x | | 8c+29-22c+14c-5=-33 | | 2x+26+4x-12=33 | | 49=9+8b | | .25k-k=23 | | -48=3+3x | | 17x^2+40x+25=0 | | 2x+3x+9=34 | | 4x-6-2x=1+3x+8x | | -6+5n=69 | | 8x-(5x-11)=39 | | -3(w-64)=-84 | | 23+2b=85 | | 7+7r=98 | | 3(5-8p)=-105 | | -10=-2(v-2) | | 2(12+8)+3x=-146 | | -3/8x-3=4/3x+11 | | 2g-15=1 | | 25x-6=-5x+3 | | 25x-6=5x+3 | | 3x+2(6x-3)=42 | | 8+6x=-10.x | | -a-3=2-2a | | w+12/4=4 | | 164=8-u |